Depression, anxiety and stress in homemakers during COVID-19 pandemic - Hardika, Jelang; Rinaldi, Martaria Rizky (Psychological Research and Intervention, 2024)
The COVID-19 pandemic has had a significant impact worldwide, affecting various aspects of life. One prominent group affected by these circumstances are homemakers"”usually women"”who bear substantial domestic responsibilities, including childcare, household chores, and family caregiving. The multitude of challenges they face can have implications for their mental well-being. This study aims to ascertain the levels of depression, anxiety, and stress among homemakers during the COVID-19 pandemic. Data collection employed the DASS-42 scale, a validated tool for measuring depression, anxiety, and stress. The study participants consisted of 88 homemakers with children. Data analysis was conducted using descriptive analysis. Results indicated that a percentage of homemakers experienced normal levels of depression (28.41%), anxiety (14.77%), and stress (37.5%). Additionally, varying degrees of depression, anxiety, and stress were present, ranging from mild to severe. These findings underscore the necessity of addressing mental health challenges specific to homemakers. Implementing support programs tailored to alleviate the mental well-being challenges faced by this demographic is crucial.